Principal leadership styles and work climate on performance of public senior secondary schools’ teachers in Ibadan metropolis (2023)
There has been a concern that counterproductive leadership styles of principals and schoolwork environment have negative effects on teachers’ job performance in secondary schools. The study examined the impact of principal leadership styles and work climate on teachers’ performance in selected public senior secondary schools in Ibadan metropolis. The study adopted correlational survey design. A sample of 270 participants was drawn from nine public senior secondary schools in selected three local government areas in the metropolis through multistage sampling techniques. The study used validated nstruments labelled “Principal’s Leadership Styles Questionnaire’ (PLSO), ‘School Work Climate Questionnaire’ (SWCQ), and ‘Teachers’ Performance Questionnaire’ (TPQ). The Cronbach Alpha test-retest reliability coefficient of 0.71, 0.68, and 0.81 were obtained respectively for the questionnaires after trail-tested among 30 teachers outside the sample. The study found that both principal leadership styles and work climate have a significant impact on the performance of public senior secondary schools’ teachers in Ibadan metropolis. The study also identified different leadership styles used by principals in public senior secondary schools in Ibadan Metropolis which were directive, supportive, participative, and achievement-oriented leadership styles. The work climate was found to be positive with teachers reporting high levels of job satisfaction and motivation. The school management board should institute conducive work climate and organise leadership development programmes for the academic staff to increase leadership competencies of principals, boost teachers’ performance in all areas of school operations, maintain the right work climate, and improve staff morale.